THE EFFECT OF PRODUCT QUALITY, BRAND IMAGE AND PRICE ON CUSTOMER LOYALTY OF MINERAL WATER IN AQUA BRAND PACKAGING - Primaraga Sumantri Indra Wicaksana; Ergo Nurpatria Kurniawan; Surya Bintarti; Iis Indarti (SEAN Institute, 2022)
This study aims to determine the effect of product quality, brand image and price on customer loyalty of mineral water in Aqua brand packaging. This research was conducted using a quantitative descriptive method, the variables in this study were 3 free variables (X) namely the influence of product quality, brand image and price and bound variables (Y) namely customer loyalty measured using primary data from questionnaires. The population in this study were consumers who would buy and consuming Aqua brand bottled water by calculating samples using a nonpropablity sampling method with an accidental sampling technique consisting of 100 respondents. The data analysis techniques used are validity test, reliability test, multiple linear analysis and t test using the SmartPLS3.3.3 program. The results showed that the quality of AQUA brand mineral water products has a weak positive effect (42%) on customer loyalty, the brand image on AQUA brand mineral water products also has a weak positive effect (48%) on customer loyalty and the price of AQUA brand mineral water products has a negative effect (-3%) on customer loyalty.